Reduction of Non‐adherent Behaviour in a Mexican‐American Adolescent with Type 2 Diabetes. (March 2014) - Piven, Emily; Duran, Rene; Stein, Franklin; Hwang, Eric
Abstract This single‐subject research aimed to evaluate the effect of occupation‐based activities to improve diabetes self‐management skills in a non‐adherent 19‐year‐old Mexican‐American adolescent transitioning to young adulthood. Using a pre‐test/post‐test design, the subject's performance was re‐evaluated with five standardized measures following an 8‐week intervention. The subject made major improvements on the Diabetes Self‐Efficacy Scale, Exercise Behaviour and in goal attainment of targeted behaviours on the basis of the Canadian Occupational Performance Measure. The Adapted Intrusiveness Rating Scale and the Social/Role Activities Limitations Scale revealed increased intrusiveness of diabetes in his life, once he finally embraced his need to prioritize diabetes self‐care. The study illuminated how a culturally sensitive, occupation‐based early intervention might potentially prevent or reduce debilitating complications in adulthood. The value of this study is its contribution to body of diabetes literature on the role of occupational therapist in secondary prevention with Mexican‐Americans. Research suggestions included expansion of single‐subject design with larger samples and higher‐level research studies with adolescents from various cultural backgrounds. Copyright © 2014 John Wiley & Sons, Ltd.